Roc the mic right : the language of hip hop culture - Alim, H. Samy (Routledge, 2006)
Using his own ethnographic research, Alim shows how Hip Hop language could be used in an educational context and presents a new approach to the study of the language and culture of the Hip Hop Nation, 'Hiphopography'.